Hubungan Faktor Sosiodemografi dengan Kejadian Anemia pada Ibu Hamil di Puskesmas Kelayan Timur Banjarmasin - Gaida Akmila; Syamsul Arifin; Lisda Hayatie (Homeostasis, 2020)
Abstract: Thei rate of anemiaain pregnant women still quite high especially in the city of Banjarmasin. Data from the Banjarmasin City Health Department in 2018, East Kelayan Puskesmas has the prevalence of anemia in pregnant women of 48.37%. Anemia in pregnant women”can be caused by several factors one of them being sociodemographic factors which include age, education, family income, and occupationi. The purpose of this study was to determine whether there is an association between sociodemographic factors and the occurrences of anemia in pregnant women at the East Kelayan Puskesmas in Banjarmasin. This study used an analytic observational method with crossssectional approachi. A sample of 50 respondents with a criteria of pure K1 was obtained by systematic random sampling technique. Data were analyzed using chi-square test and fisher’s exact test. The results showed age factor with a p value of 0.001, education with p value of 0.036, family income with p value 0.002 and occupation with a p value of 0.039. In conclusion, there is a significant association between sociodemographic factors with the occurrence of anemia in pregnant women at the East Kelayan Puskesmas in Banjarmasin with a p value of 0,000 and PR = 3,15. Keywords: sociodemography factors, anemia in pregnant women, age, education, family income, occupation. Abstrak: Anemia pada ibu hamil di Kota Banjarmasin masih cukup tinggi. Tahun 2018 anemia pada ibu hamil”ditemukan paling banyak di Puskesmas Kelayan Timur dengan prevalensi sebesar 48,37% menurut data dari Dinas Kesehatan Banjarmasin. Anemia pada ibu hamil disebabkan beberapa faktor salah satunya faktor sosiodemografi yang meliputi umur, pendidikan, pendapatan keluarga dan pekerjaan. Tujuan penelitian untuk mengetahui apakah terdapat hubungan faktor sosiodemografi (umur, pendidikan, pendapatan keluargaadannpekerjaan) dengan kejadian anemia pada ibu hamil di Puskesmas Kelayan Timur Banjarmasin. Metode penelitian observasional analitik dengan rancangan cross sectional. Sampel berjumlah 50 responden ibu hamiil dengan kriteria K1 Murni diperoleh dengan teknik systematic random sampling. Data dianalisis dengan uji chi-square dan uji fisher exact dengan hasil menunjukkan faktor umuradengan nilai p 0,001, pendidikanadengan nilai p 0,036, pendapatanakeluarga dengan nilai p= 0,002, dan pekerjaanadengan nilai p=”0,039. Kesimpulan hasil ini terdapat hubungan antara faktor sosiodemografi dengan kejadian anemia pada ibu hamil di Puskesmas Kelayan Timur Banjarmasin dengan nilai p= (0,000) PR=3,15. Kata–kata kunci: Sosiodemografi, Anemia lbu Hamil, Umur, Pendidikan, Pendapatan Keluarga, Pekerjaan.